Analysis of ABA and Fructan Contents during Onion (Allium cepa L.) Storage in the Search for Internal Sprouting Indicators - Antonino Crucitti; Wouter Kohlen; Annemarie Dechesne; Amber van Seters; Christian W. B. Bachem; Richard G. H. Immink; Olga E. Scholten (Horticulturae)
Early sprouting is a main cause of onion spoilage during storage. However, limited knowledge is available on which factors trigger sprouting. Here, this was studied in the Hyfive and Exhibition cultivars, which largely differ in sprouting time. Sprouting progress was compared to the fructan and abscisic acid (ABA) profiles in the bulb scales and basal plates. Fructan concentrations decreased in the scales from harvest time onwards in the late-sprouting cultivar Hyfive, while remaining constant in the cultivar Exhibition until internal sprouting. In the basal plates, fructan concentrations increased in both cultivars from approximately one month after harvest, but reached maximum concentrations at moments that could not be related to the difference in internal sprouting. ABA levels generally decreased in the scales of both cultivars, while increasing in their basal plates. Nevertheless, for fructans, the measured variation in ABA concentrations was not consistently associated with differences in internal sprouting. A subsequent perturbation of internal sprouting by Maleic Hydrazide treatment in the cultivar Hyfive confirmed a lack of correlation. Altogether, this indicates that fructan and ABA levels in the scales and basal plate tissue change independent of internal sprouting and cannot be regarded as predictive markers for sprouting and storability.